Drop attack during chest radiography: Case report - Botwe, B.O.; Obeng-Nkansah, J. (Radiography, 2015)
Chest radiography is the first line of thoracic imaging performed in patients with thoracic diseases. It is probably the most frequently performed type of X-ray examination. It is recommended to be performed in the full upright position except where the patient's condition will not permit. This is because the erect technique allows full expansion of the lungs, prevents engorgement of pulmonary vessels and also helps in fluid level evaluation. However, little is reported on the negative effects associated with erect radiography. Herein, we present a case of drop attack during erect chest radiography. © 2015 The College of Radiographers.
Keywords: Chest radiography; Drop attack; Erect bucky; Upright